The Relationship between Resilience and Care Burden among Parents of Students with Intellectual Disability in Golestan Province, Iran, in 2016 - Fatemeh Hassanzadeh; Hamid Hojjati (مجله پژوهش در علوم توانبخشی, 2017)
Introduction: Children with intellectual disabilities sometimes disrupt the mental health of the family and cause serious damages in their parents. Consideration of the mental health of parents of exceptional children is important due to the psychological, social, and financial burden of care and increased care burden on families of children with intellectual disabilities.